Moisture availability and its application in evaluating agriculture potential in semi-arid region - MONDAL, S.S. (MAUSAM, 1991)
The States of Punjab and. Haryana generally belong to part of arid and semi-arid regions of India. An Index known as Moisture Availability Index (MAI) has been used to demarcate it into different agroclimatic zones. The four zones Identified were named Very Low Potential (VLP) Low Potential (LP) Moderate Potential (MP) and High Potential (HP) zones. The zone V.LP had the lowest crop potential area where crops are possible in only 20.30% of the years A short duration rainfed crop of 10-12 weeks duration may be grown from zone LP while in area MP the crop growing potential is slightly more. From agricultural point of view area HP appears best suited with minimum risk. Crop prospects at one station In each zone at various risk levels have also been discussed.